Driveway lined with palm trees in the eastern hills of Santa Clara valley - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
A long row of palm trees line a driveway that leads to a white house. A woman stands halfway between the driveway and house, with a sheet of paper in her hand. Other trees, possibly cherry, are visible behind the palms.